Role of Herbal Plants on Hepatoprotective Activity - Dr. Challa Pradeep Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Liver is a vital organ plays an important role in the regulation of physiological process.it Involves in the metabolism, secretion, detoxification and digestion. Liver injury or liver dysfunction is a major health problem. Liver injury caused by various toxic chemicals like antibiotics and chemotherapeutic agents. Carbon tetrachloride CCl4, Paracetamol, thioacetamide, excessive alcohol consumption the available synthetic drugs to treat liver disorders in this condition al so cause further damage to the liver. Now a day Herbal drugs have become more popular. Herbal medicines have been used in the treatment of liver disease for a long time. A number of herbal preparations are available in the market.